Case-report of a Neonate with COVID-19 Infection: How he Has been Infected? - Javad Nazari; Zahra-Sadat Mousavi; Hasan Taher-Ahmadi; Maryam Shokrpour; Afsane Akhonzade; Pezhman Hadadi; Mojtaba Didehdar (Mashhad University of Medical Sciences, 2021)
Background: It has been indicated that pregnant women and neonates are susceptible to COVID‐19 infection. Nevertheless, the unresolved question is about the possibility of COVID‐19 infection in neonates born to COVID‐19 mothers. The present study aimed to assess the routes through which neonates may be infected with the virus: vertically or nosocomially. Case report:This study reports the case of a neonate with COVID-19 infection who became symptomatic 30 h after birth. His pharyngeal swab specimen was reported as positive by real-time reverse transcription-polymerase chain reaction (RT-PCR). It happened while the newborn's mother was tested for the COVID-19 twice, and she received negative results both times. Conclusion:According to the incubation period of COVID‐19 which is at least 1 day, the possibility of nosocomial transmission is less than other cases reported so far. Moreover, the mother had no COVID-19 symptoms during the last month of delivery. Further clinical research is necessary to determine the routes of maternal transmission of COVID-19 to neonates.